Analysis of the Financial Performance of PT Bali Bintang Sejahtera Tbk Before and After the IPO (Initial Public Offering) for the 2017-2022 Period - Refka Aprialda Fauzian*; Nenden Kostini; Nurul Mardhiah Sitio (Universitas Syiah Kuala, 2024)
This research aims to analyze the differences in financial performance of PT Bali Bintang Sejahtera Tbk at the time before and after the Initial Public Offering in 2017 to 2022. The sample of this study is the financial statement data of PT Bali Bintang Sejahtera Tbk from before and after the company conducted an Initial Public Offering (2017-2022). The research method used in testing differences before and after the company conducted an Initial Public Offering is the Paired Sample t-Test and Wilcoxon Sign Test test methods. Then to determine the increase or decrease in the company's financial performance, the average financial ratio test method is used. The results of this study indicate a significant difference in three of the four financial ratios used. The three financial ratios that experienced significant differences after the company conducted an Initial Public Offering included debt to equity ratio, net profit margin, and total assets turnover. Debt to equity ratio and net profit margin increased after the company did an Initial Public Offering, while the total assets turnover ratio decreased. Then only one financial ratio does not experience a significant difference after the company does an Initial Public Offering, namely the current ratio. But the ratio increased after the company did the Initial Public Offering